2006
DOI: 10.1097/01.shk.0000188709.04777.48
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Poly(adp-Ribose) Polymerase Reduces Cardiomyocytic Apoptosis After Global Cardiac Arrest Under Cardiopulmonary Bypass

Abstract: Cardiomyocytic apoptosis occurs after cardiopulmonary bypass (CPB) despite the use of perfusion techniques and cardioplegic solutions. Reactive oxygen species (ROS) cause single-strand DNA breaks and activate nuclear poly(ADP-ribose) polymerase (PARP), which leads to cellular damage. Therefore, the inhibition of PARP might protect cardiomyocytes from oxidative injuries. In this study, experiments were designed to determine whether a PARP inhibitor could decrease the myocardial ischemia/reperfusion injury after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Also, cardiopulmonary bypass leads to induction of apopto sis in cardiac tissue. Adding 3AB to the cardioplegic solution in cardiopulmonary bypassed hearts of rabbits diminished cardiomy ocyte apoptosis and reduced the expression of pro inflammatory cytokines (Yeh et al, 2006a).…”
Section: Transplantationmentioning
confidence: 95%
“…Also, cardiopulmonary bypass leads to induction of apopto sis in cardiac tissue. Adding 3AB to the cardioplegic solution in cardiopulmonary bypassed hearts of rabbits diminished cardiomy ocyte apoptosis and reduced the expression of pro inflammatory cytokines (Yeh et al, 2006a).…”
Section: Transplantationmentioning
confidence: 95%
“…In the following years 3-aminopenzamide was used in experimental models of stroke, renal ischemia, myocardial infarction, or heart transplantation and it was found that in all cases application of 3-aminobenzamide prior to cellular injury led to a better outcome of the examined organs (Chatterjee et al, 2000 ; Liaudet et al, 2001 ; Fiorillo et al, 2003 ; Koh et al, 2005 ). In a more recent study 3-aminobenzamide was tested in a rabbit model of CPB (Yeh et al, 2006 ). The authors could demonstrate that PARP-inhibition resulted in a significant decrease in cytokine levels and as a consequence a reduction of ROS, which in turn led to less apoptosis of cardiomyocytes and to improved contractile function of the hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is believed that remote preconditioning acts through its influence on mitochondria [1,2] similarly to ischaemic preconditioning. Our study will be one of very few trials examining its influence on mitochondrial structure and induction of apoptosis and certainly the first to study this phenomenon in human myocardium.…”
Section: Introductionmentioning
confidence: 99%